BIBLIOMETRIC ANALYSIS ON NUMERICAL LITHOFACIES IDENTIFICATION FOR RESERVOIR CHARACTERIZATION IN THE PERIOD OF 1980 -2021 - Muhamad Apriniyadi; Rosmalia Dita Nugraheni; Cahyaningratri Prima Riyandhani; Cahaya Rosyidan Rosyidan; Yarra Sutadiwiria; Imam Setiaji Ronoatmojo (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2022)
The term